An investigation of young children's science and aesthetic learning through a science aesthetic thematic curriculum: A mixed-methods study. Issue 2 (June 2020) - Chen, Yu-Ting
Aesthetic education can be integrated into students' everyday lives and into different learning areas. Its integration into science education is also valued in schools. Using mixed methods, this study investigated young children's science and aesthetic learning in a science aesthetic thematic curriculum in a preschool classroom in Taiwan. The participants were two preschool teachers and 24 five-year-old children. Data sources included the children's pre-test and post-test assessments, observations, interviews, children's worksheets and artwork, and teaching reflection notes. The preschool teachers applied Dewey's aesthetic experience to organise the thematic curriculum. The results showed that the curriculum had significant positive influences on the children's science cognitive abilities and aesthetic abilities. Most of the children increased their interest in science learning. This study provides a lens through which to examine children's science and aesthetic learning in a thematic curriculum, and also a reference for early childhood science education.